Financial performance of Nepalese insurance companies - Pradhan, Sumit; Dahal, Poshan (Nepalese Journal of Insurance and Social Security, 2021)
This study examines the financial performance of Nepalese insurance companies. The dependent variables are return on assets and earnings per share while independent variables include insurance premium, firm size, current ratio and solvency ratio. Twenty-one insurance companies among them 8 are life insurance and 13 are non-life insurance companies with 105 observations for the period of 2070/71 to 2074/75, were selected for this study. The data were collected from insurance and financial statistics published by Beema Samiti and annual reports of the selected Nepalese insurance companies. The correlation coefficient and regression models were estimated to test the significance and importance of liquidity management on financial performance of Nepalese insurance companies. The results shows that insurance premium has positive impact on return on assets and earning per share. It means that increase in insurance premium leads to increase in return on assets and earnings per share. Likewise, firm size has positive impact on return on assets and earning per share. It indicates that increase in firm size leads to increase return on assets and earnings per share. Similarly, current ratio has negative impact on return on assets. It means that increase in current ratio leads to decrease in return on assets. Likewise, solvency ratio has negative impact on return on assets. It indicates that increase in solvency ratio leads to decrease in return on assets. Similarly, current ratio have positive impact on return on assets. It means that increase in current ratio leads to increase in earnings per share. Likewise, solvency ratio has positive impact on earnings per share. It indicates that higher solvency ratio, higher would be the earnings per share. The study also concludes that insurance premium followed by current ratio and firm size is the most influencing factor that explains liquidity management and financial performance of Nepalese insurance companies.